2017
DOI: 10.1007/s00256-017-2714-6
|View full text |Cite
|
Sign up to set email alerts
|

Routine clinical knee MR reports: comparison of diagnostic performance at 1.5 T and 3.0 T for assessment of the articular cartilage

Abstract: The sensitivity, specificity, percent of articular surfaces graded concordantly, and percent of articular surfaces graded within one grade were 61.4%, 82.7%, 62.2%, and 77.5% at 1.5 T and 61.8%, 80.6%, 59.5%, and 75.6% at 3.0 T, respectively. The weighted kappa statistic was 0.56 at 1.5 T and 0.55 at 3.0 T. There was no statistically significant difference in any of these parameters between 1.5 and 3.0 T. Factors potentially contributing to the lack of diagnostic advantage of 3.0 T MRI are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Previous evidence suggests no advantage in using a 3-T rather than a 1.5-T MRI scanner, nor with dedicated high field extremity MRI. 22,23,10,24 All MRI studies were reported by generalist radiologists, with no sub-specialisation in MSK, although a previous article had suggested high accuracy in similar circumstances. 25…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Previous evidence suggests no advantage in using a 3-T rather than a 1.5-T MRI scanner, nor with dedicated high field extremity MRI. 22,23,10,24 All MRI studies were reported by generalist radiologists, with no sub-specialisation in MSK, although a previous article had suggested high accuracy in similar circumstances. 25…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…MRI of the knee was performed on a 1.5-T or 3-T platform (Philips) using a dedicated knee coil, both of which have been shown to delineate articular lesions in the knee equally well. 16 Multiplanar T1-, proton density–, and T2-weighted images were generated using a standard sports medicine protocol and reviewed by all authors. Findings were verified by a fellowship-trained pediatric musculoskeletal radiologist (J.H.K.).…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of MRI compared with the gold standard of arthroscopy for the evaluation of intra-articular pathology has been reported extensively in the literature. 14 , 15 , 16 , 17 , 18 However, MRI has been found to be less sensitive in evaluating chondral lesions and lateral meniscal injuries. 19 , 20 , 21 , 22 , 23 Furthermore, MRI may be less effective for postoperative evaluation.…”
Section: Discussionmentioning
confidence: 99%